Hypoxic secretome mesenchymal stem cells inhibiting interleukin-6 expression prevent oxidative stress in type 1 diabetes mellitus - Ayuningtyas Utami; Agung Putra; Joko Wahyu Wibowo; Amalina Nur Dina; Risky Chandra Satria Irawan (Medicinski glasnik, 2023)
Aim: Type 1 diabetes mellitus (T1DM) is an autoimmune disease characterized by the chronic inflammation of the pancreatic islets of Langerhans. Hyperglycaemia leads to suppressed antioxidant enzyme and increased inflammation in the pancreatic cell, resulting in pancreatic cell death. Hypoxic secretome mesenchymal stem cells (HS-MSCs) are soluble molecules secreted by MSCS that have the antiinflammation ability by secreting various cytokines including IL-10 and TGF-? which potent as a promising therapeutic modality for T1DM. This study aims to investigate the role of HS-MSCs in regulating superoxide dismutase (SOD) and caspase-3 gene expression in T1DM model. Methods: Twenty male Wistar rats (6 to 8 weeks old) were randomly divided into four groups (sham, control, HS-MSCs 0.5 mL and HS-MSCs 1 mL intraperitoneal treatment group). Streptozotocin (STZ) 60mg/kgBB was conducted once on day 1, HS-MSCs 0.5mL (T1) and HS-MSCs 1 mL (T2) were administrated intraperitoneally on day 7, 14, and 21 after STZ administration. The rats were sacrificed on day 28; the gene expression of SOD and IL-6 was analysed by qRT-PCR. Results: This study showed that the ratio of SOD significantly increased in HS-MSCs treatment associated with suppression of IL-6 gene expression. Conclusion: HS-MSCs administration suppresses oxidative stress and inflammation by up regulating SOD and inhibiting IL-6 to control T1DM.
Keywords: hypoxic; IL-6; secretome mesenchymal stem cells; SOD; type 1 diabetes mellitus